A Spatial‐Context‐Based Approach for Automated Spatial Change Analysis of Piece‐Wise Linear Building Elements. (24th September 2015) - Tang, Pingbo; Chen, Gaoyun; Shen, Zhenglai; Ganapathy, Ram
Abstract: Changes of designs and construction plans often cause propagative design modifications, tedious construction coordination, cascading effects of errors, reworks, and delays in project management. Among various building elements, those having piece‐wise linear geometries (i.e., connected straight line segments), such as connected straight sections of ducts in mechanical, electrical, and plumbing systems, frequently undergo spatial changes in response to the changes of their surroundings. On the other hand, the piece‐wise linear geometries pose challenges to analyzing and controlling changes in construction and facility management. State‐of‐the‐art 3D change detection algorithms often face ambiguities about which points belong to which objects when piece‐wise linear object are spacked in small spaces. This article examines a spatial‐context‐based framework that uses spatial relationships between piece‐wise linear building elements (ducts in this article) to enable fast and reliable association of 3D data with ducts in as‐designed models for supporting reliable change analysis. Three case studies showed that this framework outperformed a conventional change detection method, and could handle large dislocations of piece‐wise linear elements and occlusions.